EU Policy towards the Western Balkans: The Role of the Royaumont Process in Shaping Regional Security - Chumachenko, Olena (Вісник гуманітарних наук, 2025)
This article analyzes the Royaumont Process as the initial stage of the European Union’s policy of stabilization and conflict prevention in Southeast Europe in the period 1995–1999. The study focuses on the origins, objectives, institutional frameworks, and implementation dynamics of this initiative, emphasizing its significance as a soft security mechanism in the EU’s external action. The research identifies the Royaumont Process as the first EU effort to apply a multilevel inclusive model of post-conflict engagement, involving governments, parliaments, civil society, media, and international organizations. The paper examines the evolution of the process from political declarations to concrete cooperation in education, NGO legislation, media policy, and promotion of democratic values and regional dialogue. It is noted that the process brought together more than 30 participants, including 12 countries of Southeast Europe (Albania, Bosnia and Herzegovina, Bulgaria, Croatia, the Federal Republic of Yugoslavia, North Macedonia, Romania, Slovenia, Hungary, Turkey, Greece, and Moldova), all EU Member States, the United States, the OSCE, NATO, and the Council of Europe. The article demonstrates that the formal institutionalization of the Royaumont Process through the EU Council’s Common Position in November 1998 integrated it into the Common Foreign and Security Policy (CFSP) and secured funding mechanisms. Although not conceived as a long-term strategy, the process served as a transitional instrument between crisis management and the EU’s enlargement strategy. Its interconnection with the European Commission’s 1997 Regional Approach is also analyzed, revealing the RP’s role in laying the groundwork for the Stability Pact for South Eastern Europe (1999) and the Stabilisation and Association Process. The scientific novelty of this research lies in the first comprehensive analysis in Ukrainian historiography of the Royaumont Process as an institutionalized EU soft power initiative that bridged the post-conflict settlement phase and the long-term integration of the Western Balkans into the European political and security space.